Study of Mos Structures Using Nuclear Analytical Methods - Phuc, Tran Van; Kulik, M.; Kobzev, A. P.; Khiem, Le Hong (Communications in Physics, 2018)
The atomic concentrations and depth distribution of elements in MOS (metal oxide semiconductor) structures have been investigated using two nuclear analytical methods: Rutherford Backscattering Spectrometry (RBS) and Elastic Recoil Detection (ERD). The elements with atomic masses in range from hydrogen up to copper were identified. Their depth profiles show that a MOS structure consists from metal (Al) layer, silicon oxide layer and a silicon substrate. The heavy elements Cu, Ti were found at near-surface area of one sample with low concentrations. The transitional area between the silicon substrate and the oxide layer as well as between the metal and oxide layers was noticed. The obtained results provide valuable information about MOS structures and concurrently demonstrate possibilities of both RBS and ERD methods in material analysis.